Perceived comfort and values of travel time savings in the Rhône-Alpes Region. (June 2019) - Bouscasse, Hélène; de Lapparent, Matthieu
Abstract: Based on choice experiments conducted in the Rhône-Alpes Region (France), we estimate an Integrated Choice and Latent Variable model that addresses heterogeneity in values of interurban travel time. We evaluate how sensitivity to travel time by public transport is distributed according to the level of comfort. Comfort is modeled as a function of objective attributes and individual perceptions about it: whether a seat is guaranteed, quality of trip experience (feelings experienced), (perceived) use of travel time during the trip, and overall ease of using public transport (perceived behavioral control). The results show that the last two play a significant role in the choice of a public transport mode and that the value of time function is downward sloping with higher levels of objective and perceived comfort. We discuss public policy implications and show that the most effective measure, in terms of economic benefits, would be to optimize and target investments in seat capacity supply.